2017
DOI: 10.1128/aac.01783-16
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Modeling and Limited Sampling Strategies Based on Healthy Volunteers for Monitoring of Ertapenem in Patients with Multidrug-Resistant Tuberculosis

Abstract: Ertapenem is a broad-spectrum carbapenem antibiotic whose activity against Mycobacterium tuberculosis is being explored. Carbapenems have antibacterial activity when the plasma concentration exceeds the MIC at least 40% of the time (40% T MIC ). To assess the 40% T MIC in multidrug-resistant tuberculosis (MDR-TB) patients, a limited sampling strategy was developed using a population pharmacokinetic model based on data for healthy volunteers. A two-compartment population pharmacokinetic model was developed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The pharmacokinetic model composed in this study was shown to adequately predict ertapenem exposure in MDR-TB patients. The Monte Carlo simulation, which had a time restriction of 0 to 6 h, showed that the best-performing limited sampling strategy was at 1 and 5 h after intravenous injection (60). In another pharmacokinetic model study using prospective data from 12 TB patients, it was observed that 2 g ertapenem once daily resulted in more than a dose-proportional increase in AUC compared to the results for 1 g ertapenem once daily.…”
Section: Meropenemmentioning
confidence: 99%
“…The pharmacokinetic model composed in this study was shown to adequately predict ertapenem exposure in MDR-TB patients. The Monte Carlo simulation, which had a time restriction of 0 to 6 h, showed that the best-performing limited sampling strategy was at 1 and 5 h after intravenous injection (60). In another pharmacokinetic model study using prospective data from 12 TB patients, it was observed that 2 g ertapenem once daily resulted in more than a dose-proportional increase in AUC compared to the results for 1 g ertapenem once daily.…”
Section: Meropenemmentioning
confidence: 99%
“…Aside from the work described herein, to our knowledge, only three other groups previously utilized nonlinear functions to characterize ertapenem protein binding when conducting ertapenem PK-PD target attainment analyses (30)(31)(32). Additional strengths of these analyses were the utilization of a population PK model which included formally selected covariates and the evaluation of effect-site exposures for patients with HABP/VABP (i.e., ELF AUC values), two considerations which appear to be absent in the available literature describing ertapenem PK-PD target attainment analyses (30)(31)(32)(33)(34)(35)(36)(37). The former consideration allowed for the evaluation of simulated exposures which accounted for the impact of body size and renal function on ertapenem PK.…”
Section: Discussionmentioning
confidence: 99%
“…Adapted TCI uses Bayesian forecasting to individualize dosing regimens based on TDM data. Approaches using more traditional PK modeling software have been described by others in the field of antibiotic [ 43 , 44 ], antifungal [ 45 , 46 ] and antiviral therapy [ 47 ]. Although aTCI and more traditional TDM software use a similar theoretical framework for dosage individualisation, aTCI has some advantages.…”
Section: Discussionmentioning
confidence: 99%